The role of motivation mediates the effect of leadership style and compensation on performance - Timotius Duha; Yohanes Dakhi; Yurmanius Waruwu (Jurnal Mantik, 2023)
This study aims to investigate the effect of leadership style on performance mediated by compensation and motivation.The respondents in this study were 55 state civil servants in South Nias Regency.Smart PLS 3.0 software, used for data processing with Path analysis tools.It is known that Leadership Style has a positive and significant effect on Motivation, Compensation.and also on Performance.Motivation has a positive and significant effect on performance.Compensation has a positive and significant effect on performance.While the indirect effect of Leadership Style?Motivation?Performance.Leadership Style?Compensation?Performance, the value of the influence is relatively small, but it is unable to correct the total influence of leadership style on performance.